2016
DOI: 10.2147/ndt.s116195
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory functioning in early multiple sclerosis: Sniffin’ Sticks Test study

Abstract: IntroductionPrevious studies have shown that olfactory functioning is affected by multiple sclerosis (MS). This study assessed the level of the olfactory impairment in early MS by using the Sniffin’ Sticks Test.MethodsThis study included 30 patients with MS and 30 healthy controls. We collected demographic and clinical data from participants and administered the Sniffin’ Sticks Test.ResultsWe found no differences between the MS and control groups in odor discrimination, odor identification, and threshold discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(37 reference statements)
0
13
0
1
Order By: Relevance
“…Although olfaction is a promising biomarker for AD, it has also been identified as a potential indicator of other neurodegenerative diseases including Parkinson’s disease (PD) [ 59 ], Huntington’s disease [ 60 ], multiple sclerosis (MS) [ 61 ], and amyotrophic lateral sclerosis (ALS) [ 62 ]. Therefore, future work in this area needs to focus upon improving the specificity of olfaction as a biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although olfaction is a promising biomarker for AD, it has also been identified as a potential indicator of other neurodegenerative diseases including Parkinson’s disease (PD) [ 59 ], Huntington’s disease [ 60 ], multiple sclerosis (MS) [ 61 ], and amyotrophic lateral sclerosis (ALS) [ 62 ]. Therefore, future work in this area needs to focus upon improving the specificity of olfaction as a biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation into whether different domains of olfaction (odour identification, recognition, or discrimination) are impaired to different extents in different diseases is also required. For example, odour threshold scores were found to be altered in MS versus control patients, whereas other olfactory parameters were unaltered [ 61 ]. In AD, odour identification appears to be the most reliable indicator of disease [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 Studies have used different methodologies but associations with age, sex, 430,441,447,453 and mood disorders 429,434,435,440,441 have been observed. Association with disease activity, 427,435,437,441,442,444,445,[447][448][449][450]452,453,[457][458][459][460]462,467,468,470,471,473,474 neurological manifestations, 435,[437][438][439][440][441][442][443]445,447,450,452,453,[457][458]…”
Section: G Related To Underlying Systemic Disease 1 Autoimmunementioning
confidence: 99%
“…9 On the other hand, few studies showed no difference in odor identification between patients and control group 10 and no correlation with the Expanded Disability Status Scale (EDSS) and disease duration. 11 Therefore, the aim of the present study was to compare olfactory function between patients with RRMS and controls with a short screening tool-the Sniffin' Sticks Identification Test (SSIT). Assuming that the hyposmia was more common in RRMS, we also searched for association between olfactory dysfunction in SSIT and clinical and radiological features of the disease, such as a number of relapses, MRI characteristics, cognitive function, and results of cerebrospinal fluid (CSF) analyses.…”
Section: Introductionmentioning
confidence: 99%